Dynamic response of GFRP-reinforced UHPC beams under close-in blast loading. (November 2022) - Yan, Junbo; Liu, Yan; Bai, Fan; Ni, Xiangyong; Xu, Yingliang; Yan, Zichen; Huang, Fenglei
Graphical abstract: Highlights: Field tests and a well-verified numerical model reveal the failure mechanism of UHPC-GFRP beams subjected to close-in blast loads. The UHPC-GFRP beam exhibited less deformation and a greater rebound displacement than the UHPC-NSS and UHPC-HSS beams. The UHPC-GFRP beam experienced similar local damage compared to traditional steel RC beams. The blast resistance decreased when the diameter of the GFRP rebar increased from 16 mm to 20 mm due to reduced bonding strength. Abstract: Combined use of ultrahigh-performance concrete (UHPC) with glass fiber reinforced polymer (GFRP) reinforcement has the potential for further blast resistance enhancement of reinforced concrete (RC), due to the improved toughness of UHPC and the high strength-to-weight ratio of GFRP. This paper aims to fill the gap on the effectiveness of GFRP bars on the blast response of UHPC beams. The blast resistance of UHPC beams built with GFRP bars (UHPC-GFRP beams) is experimentally and numerically investigated in this paper. In the experimental scheme, twelve beams strengthened with various types of concrete and reinforcement are tested under near-field explosions. The properties of UHPC beams reinforced with GFRP bars are compared with specimens reinforced with normal-strength steel (NSS) and high-strength steel (HSS) bars. GFRP bars reduce the maximum displacements, which enhances the blast performance of UHPC beams. However, reinforcing UHPC beams with GFRP bars results in large rebound displacements. In addition, the coupled finite element model is adopted to predict the response of test beams. The numerical method using LS-DYNA achieves reasonable accuracy. Moreover, the damage process, energy characteristics, reaction forces, stress response and the effect of the compressive reinforcement are examined to better depict the damage mechanism of the UHPC-GFRP beams.